Cytochrome P450 epoxygenase‐derived 5, 6‐epoxyeicosatrienoic acid relaxes pulmonary arteries in normoxia but promotes sustained pulmonary vasoconstriction in hypoxia. (22nd June 2020) - Strielkov, Ievgen; Krause, Nicole C.; Knoepp, Fenja; Alebrahimdehkordi, Nasim; Pak, Oleg; Garcia, Claudia; Ghofrani, Hossein A.; Schermuly, Ralph T.; Seeger, Werner; Grimminger, Friedrich; Sommer, Natascha; Weissmann, Norbert
Abstract: Aims: The aim of the study was to investigate the role of cytochrome P450 (CYP) epoxygenase‐derived epoxyeicosatrienoic acids (EETs) in sustained hypoxic pulmonary vasoconstriction (HPV). Methods: Vasomotor responses of isolated mouse intrapulmonary arteries (IPAs) were assessed using wire myography. Key findings were verified by haemodynamic measurements in isolated perfused and ventilated mouse lungs. Results: Pharmacological inhibition of EET synthesis with MS‐PPOH, application of the EET antagonist 14, 15‐EEZE or deficiency of CYP2J isoforms suppressed sustained HPV. In contrast, knockdown of EET‐degrading soluble epoxide hydrolase or its inhibition with TPPU augmented sustained HPV almost twofold. All EET regioisomers elicited relaxation in IPAs pre‐contracted with thromboxane mimetic U46619. However, in the presence of KCl‐induced depolarization, 5, 6‐EET caused biphasic contraction in IPAs and elevation of pulmonary vascular tone in isolated lungs, whereas other regioisomers had no effect. In patch‐clamp experiments, hypoxia elicited depolarization in pulmonary artery smooth muscle cells (PASMCs), and 5, 6‐EET evoked inward whole cell currents in PASMCs depolarized to the hypoxic level, but not at their resting membrane potential. Conclusions: The EET pathway substantially contributes to sustained HPV in mouse pulmonary arteries. 5, 6‐EET specifically appears to be involved in HPV, as it is the only EET regioisomer able to elicit not only relaxation, but also sustained contraction in these vessels. 5, 6‐EET‐induced pulmonary vasoconstriction is enabled by PASMC depolarization, which occurs in hypoxia. The discovery of the dual role of 5, 6‐EET in the regulation of pulmonary vascular tone may provide a basis for the development of novel therapeutic strategies for treatment of HPV‐related diseases.